“Estimación del índice de mérito total del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia Eloy Alfaro” - Bernal Largo, Wendy Lisseth (2023)
The research was carried out in the parish of Eloy Alfaro, Latacunga canton belonging to the province of Cotopaxi with the purpose of estimating the total genetic merit index, through the collection of data so that each owner is aware of the genetic values of their animals. We used an analytical and descriptive type of study in which we conducted visits, surveys and records to the residents of the parish that are part of the project, with a total population of 101 animals found in the different neighborhoods of the parish, They provided us with information about their animals and their management practices in which we were able to observe that most of the animals are managed based on sogueo, in addition to the feed administered is not good because the forage with which they feed them is scarce and they resort to the purchase of feed, the expenses associated with the production are greater than the profits obtained. The income that the producers receive from the sale of milk is $416, of which $48.19 is destined to milk production expenses in a period of 3 months, thus giving a total profit of $368, with an average cost of milk production of 22 ctvs. On the other hand, in terms of genetic value, a daily weight gain of 229 gr/d is shown. In the genetic evaluation of each animal there is an average of 3544 kg/lactation with a density of 1033 g/ml. Regarding the responses to selection, the following heritability values are presented, daily weight gain 143 gr. Additionally, it is expected that future generations will produce 1811 kg/lactation and a density with a value of 1030 g/ml, being these the highest values in the parish.